Red blood cell transfusion probability and associated costs in neurosurgical procedures - Barth, Martin; Weiß, Christel; Schmieder, Kirsten (Acta neurochirurgica, 2018)
The extent of red blood cell units (RBC) needed for different neurosurgical procedures and the time point of their administration are widely unknown, which results in generously cross-matching prior to surgery. However, RBC are increasingly requested in the aging western populations, and blood donations are significantly reduced. Therefore, the knowledge of the extent and time point of administration of RBC is of major importance.
Gesehen am 20.10.2020